Digging into the Dark Ages : early medieval public archaeologies - Williams, Howard, 1972-; Clarke, Pauline (Access archaeology., 2020)
What does the 'Dark Ages' mean in contemporary society? Tackling public engagements through archaeological fieldwork, heritage sites and museums, fictional portrayals and art, and increasingly via a broad range of digital media, this is the first-ever dedicated collection exploring the public archaeology of the Early Middle Ages.